Pancracine, a Montanine-Type Amaryllidaceae Alkaloid, Inhibits Proliferation of A549 Lung Adenocarcinoma Cells and Induces Apoptotic Cell Death in MOLT-4 Leukemic Cells - Koutova, Darja; Havelek, Radim; Peterova, Eva; Muthna, Darina; Královec, Karel; Breiterova, Katerina; Cahlikova, Lucie; Rezacova, Martina (MDPI, 2021)
Pancracine, a montanine-type Amaryllidaceae alkaloid (AA), is one of the most potent compounds among natural isoquinolines. In previous studies, pancracine exhibited cytotoxic activity against diverse human cancer cell lines in vitro. However, further insight into the molecular mechanisms that underlie the cytotoxic effect of pancracine have not been reported and remain unknown. To fill this void, the cell proliferation and viability of cancer cells was explored using the Trypan Blue assay or by using the xCELLigence system. The impact on the cell cycle was determined by flow cytometry. Apoptosis was evaluated by Annexin V/PI and by quantifying the activity of caspases (-3/7, -8, and -9). Proteins triggering growth arrest or apoptosis were detected by Western blotting. Pancracine has strong antiproliferative activity on A549 cells, lasting up to 96 h, and antiproliferative and cytotoxic effects on MOLT-4 cells. The apoptosis-inducing activity of pancracine in MOLT-4 cells was evidenced by the significantly higher activity of caspases. This was transmitted through the upregulation of p53 phosphorylated on Ser392, p38 MAPK phosphorylated on Thr180/Tyr182, and upregulation of p27. The pancracine treatment negatively altered the proliferation of A549 cells as a consequence of an increase in G1-phase accumulation, associated with the downregulation of Rb phosphorylated on Ser807/811 and with the concomitant upregulation of p27 and downregulation of Akt phosphorylated on Thr308. This was the first study to glean a deeper mechanistic understanding of pancracine activity in vitro. Perturbation of the cell cycle and induction of apoptotic cell death were considered key mechanisms of pancracine action.
Pankracin, alkaloid čeledi Amaryllidaceae montaninového typu, inhibuje proliferaci buněk plicního adenokarcinomu A549 a indukuje apoptózu u leukemických buněk MOLT-4
Keywords: amaryllidaceae alkaloids; pancracine; cytotoxicity; antiproliferative activity; cell cycle arrest; apoptosis; amarylkovité alkaloidy; pankracin; cytotoxicita; antiproliferační aktivita; zástava buněčného cyklu; apoptóza